Detection and quantification of aflatoxins in spices stored in different food packaging materials. (March 2023) - Abrar, Muhammad; Ahsan, Samreen; Nadeem, Muhmmad; Liaqat, Atif; Chughtai, Muhmmad Farhan Jahangir; Farooq, Muhammad Adil; Mehmood, Tariq; Khaliq, Adnan; Siddiqa, Ayesha
Abstract: The current research aims to examine the effect of storage conditions on aflatoxin production in different spices. For this purpose, different samples of spices (Red chilies, Black peppers, and Cumin) were packaged in different packing materials, high-density polyethylene bags, and jute bags and stored in a controlled environment at 25 °C temperature with varying relative humidity conditions (RH: 65%, 75%, 85%) and evaluated for moisture content, total phenolics, Aspergillus count, total fungal count, and aflatoxins. Packaging materials and storage conditions showed a gradual increase in the tested parameters with increased humidity. The mean Aspergillus count for red chillies, cumin, and black pepper was lowest in HDPE (2.20 × 10 2, 3.00 × 10 1 and 4.50 × 10 1, respectively) with 65% moisture content. Aflatoxins were also detected highest (3.33 ppb) in the jute package with 85% moisture content as compared to HDPE (0.9 ppb) for red chilies. Evaluated results proved that spices packed and stored in polyethylene bags retained better quality at 65% relative humidity, where aflatoxin levels were not detected even at 90 days storage period. However, the aflatoxin level was observed lowest (0.13 ppb in cumin) after 120 days of storage. Thus, the utilization of polyethylene packages as compared to jute bags has a better effect on the safety and quality of spices by controlling aflatoxin production during storage. Highlights: Examine the effect of storage conditions on aflatoxin production in different spices. Spices packed and stored in polyethylene bags retained better quality at 65% relative humidity. Among the spices, red chillies contain a higher level of aflatoxin followed by black pepper and cumin. Polyethylene packages as compared to jute bags have better effect on the safety and quality of spices.